Crustacean hyperglycemic hormone of Portunus trituberculatus: evidence of alternative splicing and potential roles in osmoregulation - Sun, Dongfang (Cell Stress Chaperones, 2019)
The crustacean hyperglycemic hormone (CHH) gene of Portunus trituberculatus (Pt-CHH) consists of four exons and three introns spanning 3849 bp in size and generating two mature mRNA, Pt-CHH1, and Pt-CHH2. The primary gene transcript produces a cDNA encoding for the putative Pt-CHH2 from exons 1, 2, 3, and 4 and an alternative transcript encodes for a putative Pt-CHH1 peptide from exons 1, 2, and 4. A promoter fragment of about 3 kb was obtained by genomic walking. The tissue-specific expression pattern is examined by reverse transcriptase chain reaction, and the results show that Pt-CHH1 is detected in the eyestalk, brain, muscle, and blood. However, Pt-CHH2 is detected in the ganglia thoracalis and gill. The results indicate that the expression of Pt-CHH2 in the gill might suggest a potential role in osmoregulation. The Pt-CHH transcript level in the gill increases when the crab is exposed to low salinity. The injection of dsRNA for Pt-CHH causes a significant reduction in Pt-CHH2 transcript level and the activity of Na(+)/K(+)-ATPase, and carbonic anhydrase (CA) show a serious decrease. In conclusion, this study provides molecular evidence to support the osmoregulatory function of Pt-CHH2.